Ring-Opening Polymerization of rac-Lactide with Aluminum Chiral Anilido-Oxazolinate Complexes - Bian, Shi (American Chemical Society, 2014)
[Image: see text] A series of dimethylaluminum complexes (L(1a–i))AlMe(2) (2a–i, where HL(1a–i) = 2-(2′-ArNH)phenyl-4-R(1)-oxazoline) bearing chiral, bidentate anilido-oxazolinate ligands have been prepared and characterized. Six of the complexes, in the presence of an alcohol cocatalyst, are shown to be active initiators for the stereoselective ring-opening polymerization of rac-lactide in toluene solution and under bulk conditions, yielding polylactides with a range of tacticity from slightly isotactic to moderately heterotactic. The reactivity and selectivity of these catalysts are discussed on the basis of the effect of their substituents.